2011
DOI: 10.1055/s-0039-1698906
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Characteristics of Mesiodens in a Turkish Patient Population

Abstract: Objectives:The aim of this study was to investigate the frequency and characteristics of mesiodens among a group of orthodontic patients in Turkey.Methods:A retrospective study was performed using panoramic radiographs of 3,351 patients ranging in age from 8 to 16 subjected to dental treatment in the Department of Oral and Maxillofacial Radiology and Department of Orthodontics (Erzurum, Turkey) between 1996 and 2008. All medical and demographic data (age and sex) were obtained from the files. Descriptive chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
39
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 16 publications
9
39
3
5
Order By: Relevance
“…The reason for this is that the supplemental teeth in the form of natural teeth are often confused with permanent teeth, and the patient's family might think that the central teeth have erupted. 11 The majority (76.8%) of the mesiodens in the current study were in the vertical position, consistent with previous studies. Of the 82 mesiodens, 65 were vertical (76.8%), nine were inverted (12.1%), and eight were horizontal (10.9%).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The reason for this is that the supplemental teeth in the form of natural teeth are often confused with permanent teeth, and the patient's family might think that the central teeth have erupted. 11 The majority (76.8%) of the mesiodens in the current study were in the vertical position, consistent with previous studies. Of the 82 mesiodens, 65 were vertical (76.8%), nine were inverted (12.1%), and eight were horizontal (10.9%).…”
Section: Discussionsupporting
confidence: 92%
“…They can be categorized as single (one mesiodens) or multiple (2, 3, or 4 mesiodens) . Gündüz et al, Kazancı et al, and Kocatas Ersin et al found one mesiodens in 76.8% of patients, and two mesiodens in 23.1%, one in 80%, and two in 20%, and one in 41.72% and two in 58.82% of patients, respectively . In the present study, one mesiodens in 84.5% (N = 60) of patients and two mesiodens in 15.4% (N = 11) of patients were found, and more than two mesiodens were not found in any of the patients.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The mean age of patients with mesiodens in the present study (82.52 ± 12.67 months) was similar to that in previous studies. Children in this age group generally undergo assessments for normal tooth eruption and treatment for delayed or failed eruption of the maxillary central incisors; therefore, mesiodens is commonly discovered during this period.…”
Section: Discussionsupporting
confidence: 86%